Creation of an OBE Model PO Attainment Tool - Lokesh Kumar Bansal, Pankaj Kumar Mishra,Shweta Sachdeva, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper is focused on the strategy of outcome-based education (OBE) approach to boost the quality of education. This approach emphasizes on pre-defined attributes required in a graduate engineer. Based on evaluation of OBE, the attainment process of programme outcome (PO) is defined for qualitative education. To show that an outcome has been met, the OBE requires evidence of evaluation. An evaluation framework has been designed and developed by considering the engineering stream students. The tools of attainment are built by considering different parameters of the respective curriculum to measure the attainment of POs. In the OBE system, there is no single specified technique of teaching and assessment to achieve the specified outcomes..